1989
DOI: 10.1016/0014-5793(89)80756-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C is crucial in signal transduction during IFN‐γ induction in endothelial cells

Abstract: We have demonstrated that IFN-7, a potent peptide mediator in inflammatory responses, operates via the protein kinase C dependent transduction pathway in the induction of class II MHC antigens on rat microvascular endothelial cells. Stimulators of protein kinase C, like PMA, replaced IFN-~, in the induction of MHC class II on endothelial cells in a dose-dependent manner. Selective enzyme inhibitors of protein kinase C, H-7 as well as sphingosine down-regulated the IFN-7 induced class II expression in a dose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 16 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…Several lines of evidence in our study support the direct role of cAMP as a second messenger in [28, 291, H7 has been reported to be able to totally block the IFN-y induced PKC activation in endothelial cells [27].…”
Section: Discussionsupporting
confidence: 86%
“…Several lines of evidence in our study support the direct role of cAMP as a second messenger in [28, 291, H7 has been reported to be able to totally block the IFN-y induced PKC activation in endothelial cells [27].…”
Section: Discussionsupporting
confidence: 86%
“…Relatively little is known about the molecular mechanisms of IFN^y induction of class II genes. Studies on second messenger systems have implicated protein kinase C (PKC) (Fan et al, 1988;Mattila et al, 1989;Nezu et al, 1990), Ca2+-dependent processes (Koide et al, 1988; Celada and Maki,1991), cAMP (Frohman et al, 1988;Basta et al, 1989) and changes in intracellular pH as important second messengers in the IFN-y regulation of class II genes (Prpic et al, 1989). However, these observations vary between different cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work with PMA had shown that it stimulates protein kinase C in many cell types, like in normal white cells, hematopoietic tumor cells and in endothelial cells [20,21]. Concomitantly PMA induces many cell types to adhere onto plastic surfaces, to each other and to endothelial monolayers [18].…”
Section: Discussionmentioning
confidence: 99%